Effect of combined therapy by pinaverium bromide and itopride hydrochloride on clinical semiology and quality of life of patients with combination of constipation variant of irritable bowel syndrome and functional dyspepsia - O. V. Krapivnaya; S. A. Alekseyenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To estimate the effect of combined treatment by pinaverium bromide and itopride hydrochloride on clinical semiology and quality of life of patients with combination of constipation-predominant variant of irritable bowel syndrome (IBS-C) with postprandial distress syndrome (PDS).Material and methods. Overall 49 patients with IBS-C (Rome criteria III) were investigated, 31 of them also had accompanying PDS (Rome criteria III). Fourteen patients with combination of IBS-C and PDS (group I) for 4 wks received combined treatment by pinaverium bromide and itopride hydrochloride. Monotherapy by pinaverium bromide for 4 wks was carried out in 17 patients with combination of IBS-C and PDS (group II) and 18 patients with IBS-C (group III). Both symptoms and parameters of quality of life (SF-36) were estimated prior to onset of treatment and in 4 wks after its termination.Results. Combined therapy by pinaverium bromide and itopride hydrochloride for 4 wks in comparison to monotherapy by pinaverium bromide promoted more prominent reduction of abdominal pain intensity (p<0,001), meteorism (p<0,001), epigastric heaviness (p<0,001), complete disappearance of nausea and belching in many patients with combination of IBS-C and PDS. Treatment by pinaverium bromide in combination with itopride hydrochloride was characterized by absence of serious side effects and resulted in significant improvement of quality of life (p<0,001).Conclusions. Application of the combined therapy including spasmolytic drug pinaverium bromide and prokinetic agent itopride hydrochloride for patients combination of IBS-C and PDS significantly increased efficacy of relief of clinical symptoms of combined disease and improved quality of life of patients.